Human leukocyte antigen associations with renal function among ethnic minorities in the United Kingdom. (5th November 2020) - Lowe, Marcus; Payton, Antony; Verma, Arpana; Gemmell, Isla; Worthington, Judith; Hamilton, Patrick; Ollier, William; Augustine, Titus; Poulton, Kay
Abstract : Human leukocyte antigens (HLA) have been associated with renal function, but previous studies report contradictory findings. There has been a lack of research into how HLA affects renal function in Black, Asian and Minority Ethnic (BAME) people in the UK, despite BAME people being disproportionately affected by renal dysfunction. This study included >27 000 UK Biobank subjects of six ethnicities (>12 100 Irish, >5400 Indian, >4000 Black Caribbean, >3000 Black African, >1600 Pakistani, and >1400 Chinese) aged 39 to 73. Subjects' high‐resolution HLA genotypes were imputed using HLA*IMP:02 software. Regression analysis was used to compare 108 imputed HLA alleles with two measures of estimated glomerular filtration rate (eGFR): one based on serum creatinine; one based on serum cystatin. Secondary analysis compared CKD stage 2 subjects to healthy controls. Nine imputed HLA alleles were associated with eGFR (adjusted P < .05). Six associations were based on creatinine in Black African subjects: HLA‐B*53:01 (beta = −2.628, adjusted P = 4.69 × 10 −4 ); C*04:01 (beta = −1.667, adjusted P = .0269); DPA1*02:01 (beta = −1.569, adjusted P = .0182); and DPA1*02:02 (beta = −1.716, adjusted P = .0251) were linked to decreased renal function, while DRB1*03:01 (beta = 3.200, adjusted P = 3.99 × 10 −3 ) and DPA1*01:03 (beta = 2.276, adjusted P = 2.31 × 10 −5 ) were linked to increased renal function. Two of these ( HLA‐B*53:01 and C*04:01 ) are commonly inherited together. In Irish subjects, HLA‐DRB1*04:01 (beta = 1.075, adjusted P = .0138) was linked to increased eGFR (based on cystatin); in Indian subjects, HLA‐DRB1*03:01 (beta = −1.72, adjusted P = 4.78 × 10 −3 ) and DQB1*02:01 (beta = −1.755, adjusted P = 2.26 × 10 −3 )were associated with decreased eGFR (based on cystatin). No associations were found in the other three ethnic groups. Nine HLA alleles appear to be associated with kidney function in BAME people in the UK. This could have applications for the diagnosis and treatment of renal disease and could help reduce health inequalities in the UK.